GROWING UP WITHOUT DAD: EGO DAN KOMUNIKASI KELUARGA YANG MEMPENGARUHI KOMITMEN DAN SERIOUS RELATIONSHIPS - Zahra Hasna; Siti Komariah; Puspita Wulandari (Universitas Negeri Medan, 2025)
The phenomenon of growing up without a father is increasingly prevalent in modern Indonesian families. This has an impact on individual ego development, family communication, and readiness for commitment in adult romantic relationships. A systematic literature review method was used in this study to examine the relationship between these three variables. This study conducted a search of the latest literature from journals on family sociology and developmental psychology. The results show that father absence causes identity crises, emotional regulation disorders, and unresponsive family communication. Ultimately, this hinders the formation of stable commitments and increases the risk of unhealthy relationships. These results are reinforced by Ralph Linton's role theory, which states that adult relationship patterns are shaped by imbalances in family social roles. This study supports an integrative conceptual model for psychosocial interventions in fatherless families.